871–873: Constantine VII Porphyrogennetos on the Revenge of Soldanos of Bari (Transmediterranean History, 2025)
The article deals with a passage in Constantine VII Porphyrogennetos’ De administrando imperio that contains a rather idiosyncratic description of the conquest of Muslim-ruled Bari and its aftermath. Complementing southern Italian Latin-Christian as well as Arabic-Islamic texts on the end of the emirate in the early 870s, Constantine’s version highlights the contribution of Byzantine forces, claims that Louis II of Italy and the Langobard nobles of southern Italy were outwitted by the amīr Sawdān, and presents the entire reconquest of Bari as the successful re-integration of a lost city into the Eastern Roman Empire. Engaging with the narrative’s sources and parallel evidence, the article reveals the constructed bias of a passage that may, nonetheless, shed additional light on Christian–Muslim relations in southern Italy of the late ninth century.
Keywords: Constantine VII; Louis II; Sawdān; Langobards; emirate; Bari; Apulia; Italy; raids; conquest; Carolingians; Byzantines; Carolingian–Byzantine relations